Novel Exosome-Targeted CD4+ T Cell Vaccine Counteracting CD4+25+ Regulatory T Cell-Mediated Immune Suppression and Stimulating Efficient Central Memory CD8+ CTL Responses - Siguo Hao; Yongqing Liu; Jinying Yuan; Xueshu Zhang; Tianpei He; Xiaochu Wu; Yangdou Wei; Deming Sun; Jim Xiang (2007)
T cell-to-T cell Ag presentation is increasingly attracting attention. In this study, we demonstrated that active CD4+ T (aT) cells with uptake of OVA-pulsed dendritic cell-derived exosome (EXO(OVA)) express exosomal peptide/MHC class I and costimulatory molecules. These EXO(OVA)-uptaken (targeted) CD4+ aT cells can stimulate CD8+ T cell proliferation and differentiation into central memory CD8+ CTLs and induce more efficient in vivo antitumor immunity and long-term CD8+ T cell memory responses than OVA-pulsed dendritic cells. They can also counteract CD4+25+ regulatory T cell-mediated suppression of in vitro CD8+ T cell proliferation and in vivo CD8+ CTL responses and antitumor immunity. We further elucidate that the EXO(OVA)-uptaken (targeted)CD4+ aT cell's stimulatory effect is mediated via its IL-2 secretion and acquired exosomal CD80 costimulation and is specifically delivered to CD8+ T cells in vivo via acquired exosomal peptide/MHC class I complexes. Therefore, EXO-targeted active CD4+ T cell vaccine may represent a novel and highly effective vaccine strategy for inducing immune responses against not only tumors, but also other infectious diseases.